Persistence of passive immunity to porcine parvovirus - Too, H. L.; Love, R. J. (Wiley, 1985)

(untitled)
Maternally derived antibody to porcine parvovirus (PPV) has been shown to prevent the development of active immunity following infection or vaccination (Johnson et al 1976; Paul et aI1980).